Chemical cleaning agents and bonding to glass-fiber posts - Ana Paula Rodrigues Gonçalves; Aline de Oliveira Ogliari; Patrícia dos Santos Jardim; Rafael Ratto de Moraes (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The influence of chemical cleaning agents on the bond strength between resin cement and glass-fiber posts was investigated. The treatments included 10% hydrofluoric acid, 35% phosphoric acid, 50% hydrogen peroxide, acetone, dichloromethane, ethanol, isopropanol, and tetrahydrofuran. Flat glass-fiber epoxy substrates were exposed to the cleaners for 60 s. Resin cement cylinders were formed on the surfaces and tested in shear. All treatments provided increased bond strength compared to untreated control specimens. All failures were interfacial. Although all agents improved the bond strength, dichloromethane and isopropanol were particularly effective.